Circulating Tumor DNA in Head and Neck Squamous Cell Carcinoma: Association with Metabolic Tumor Burden Determined with FDG-PET/CT - Silvoniemi A; Laine J; Aro K; Nissi L; Back L; Schildt J; Hirvonen J; Hagström J; Irjala H; Aaltonen LM; Seppänen M; Minn H (MDPI, 2025)
Simple Summary The detection of circulating tumor DNA (ctDNA) has gained increasing interest in precision oncology. In head and neck squamous cell carcinoma (HNSCC), a heterogenous mutational landscape contributes to substantial challenges in prognostic and predictive assessment. We report our observations of associations between quantitative parameters in ctDNA and the metabolic tumor burden determined based on FDG-PET/CT. We found that maximum variant allele frequency (VAF) in venous liquid biopsy correlated positively with metabolic tumor burden measured with whole-body total lesion glycolysis (TLG). The prognostic significance of this PET parameter has been documented repeatedly in previous meta-analyses in HNSCC. Our findings indicate that a complex mutational landscape contributes to this metabolic burden. A combination of ctDNA detection and FDG-PET/CT may provide added value for the prognostic and predictive evaluation of HNSCC in the setting of initial diagnosis and follow-up after definitive therapy. Background: The detection of circulating tumor DNA (ctDNA) with next-generation sequencing (NGS) in venous blood is a promising tool for the genomic profiling of head and neck squamous cell carcinoma (HNSCC). The association between ctDNA findings and metabolic tumor burden detected with FDG-PET/CT imaging is of particular interest for developing prognostic and predictive algorithms in HNSCC. Methods: Twenty-six prospectively enrolled HNSCC patients were eligible for further analysis. All patients underwent tumor tissue and venous liquid biopsy sampling and FDG-PET/CT before definitive oncologic treatment. An NGS-based commercial panel was used for a genomic analysis of the samples. Results: Maximum variant allele frequency (VAF) in blood correlated positively with whole-body (WB) metabolic tumor volume (MTV) and total lesion glycolysis (TLG) (r = 0.510, p = 0.008 and r = 0.584, p = 0.002, respectively). A positive liquid biopsy was associated with high WB-TLG using VAF & GE; 1.00% or & GE;5.00% as a cut-off value (p = 0.006 or p = 0.003, respectively). Additionally, ctDNA detection was associated with WB-TLG when only concordant variants detected in both ctDNA and tissue samples were considered. Conclusions: A high metabolic tumor burden based on FDG imaging is associated with a positive liquid biopsy and high maximum VAF. Our findings suggest a complementary role of metabolic and genomic signatures in the pre-treatment evaluation of HNSCC.